How Important Is Future Teachers' "Connectedness to Nature"? Adaptation and Validation of the Connectedness to Nature Scale - Dunja Anđić; Lorena Šuperina (MDPI AG, 2021)
The teacher plays a key role in fostering sustainability and implementing Education for Sustainable Development at school. This paper presents a study aimed at adapting and validating a shorter version of the Connectedness to Nature Scale (CNS) to measure student future teachers' connectedness to nature. The scale has been translated into Croatian in an abbreviated form and applied to a specific sample of students from the Faculty of Teacher Education in Rijeka, Croatia (N = 138). One of the tasks was to examine whether there are statistically significant differences among students regarding their membership in eco-associations and previous participation in an Environmental Education/Education for Sustainable Development (EE/ESD) course. A special research objective was to determine the extent to which the current education and membership in an eco-association explain the connectedness to nature. In addition to the indicated research limitations, the results confirmed the significant measured characteristics of the scale. Education has so far proved to be a predictor of connectedness to nature. Additionally, the results showed that membership in an eco-association is a predictor of connectedness to nature. Based on the obtained results, it is possible to conclude that the connectedness to nature must be further explored, especially in the context of the initial education of future teachers, as a possible prerequisite for a successful practice of Education for Sustainable Development in schools.